PROGRESA and its impacts on the welfare of rural households in Mexico - Skoufias, Emmanuel (International Food Policy Research Institute, 2005)
This document synthesizes the findings contained in a series of reports prepared by IFPRI for PROGRESA between November 1998 and November 2000... PROGRESA is one of the major programs of the Mexican government aimed at developing the human capital of poor households. Targeting its benefits directly to the population in extreme poverty in rural areas, PROGRESA aims to alleviate current and future poverty levels through cash transfers to mothers in households.... One of the most important contributions of IFPRI’s evaluation of PROGRESA has been the continuation of the program in spite of the historic change in the government of Mexico in the 2000 elections. The overwhelming (and unprecedented) evidence that a poverty alleviation program shows strong signs of having a significant impact on the welfare and human capital investment of poor rural families in Mexico has contributed to the decision of the Fox administration to continue with the program and to expand its coverage in the poor urban areas of the country after some improvements in the design of the program.... The majority of the improvements in the design of PROGRESA (renamed Oportunidades by the Fox administration) were based on findings of the evaluation of PROGRESA that revealed areas of needed improvements in some of the structural components and the operation of the program... Yet in spite of these improvements in the program, the evaluation findings suggest that some issues remain to be resolved.